ANALYSIS OF THE MANAGEMENT ASPECT OF PRIMARY SCHOOL QUALITY IMPROVEMENT - Sunaengsih, Cucun; Thahir, Muthahharah; Tamam, Badrud; Safitri, Bunga (Universitas Pendidikan Indonesia, 2018)
The primary aim of this study is to discover how quality improvement management in primary school, in terms of students, educators, headmasters, curriculum, learning process, and infrastructures, is implemented. The present study employs qualitative research method, which is descriptive, using analysis, referring to data, and utilizing existing theories as supporting materials. The primary data source in a qualitative study is the informant. Data is collected through interviews, observation, and documentation. The findings of this study indicate that education quality improvement management in a primary school in West Java, Indonesia is quite good. However, there are some aspects that need to be improved to achieve high quality education, particularly the facilities and infrastructure aspect.